PATHOLOGY OF EQUINE INFECTION WITH SALMONELLA TYPHIMPRIUM VAR COPENHAGEN - Eabasha , F.G.; Al- Awadi, K.K (The Iraqi Journal of Veterinary Medicine, 2022)
Twelve horses were divided into three equal groups. Group I animals were inoculated orally with (3.7 X1012)CFU of a highly virulent strain of Salmonella typhimurium 3,;a_r cop§_n__hagen. Group 11 animals were inoculated orally with 2 doses of Salmonella and then challenged with a high dose. Group III horses, served as non - infected control. ‘The main lesions were primarily conﬁned to the digestive tract and were characterized by catarrhal enteritis. Pseudornembrane covered the mucosa of the ileum at the ileo — cecal Valve region.Histopathological examination revealed marked rnononuclear cellular inﬁltration in the lamina propria and occasionally necrosis and edema in the mucosa and submucosa of the intestine.